Courses for Kids
Free study material
Offline Centres
Store Icon

How do you solve \[7n - 5 = 5n + 7\]?

Last updated date: 19th Jul 2024
Total views: 382.2k
Views today: 10.82k
382.2k+ views
Hint: In the given problem we need to solve this for ‘n’. We can solve this using the transposition method. The common transposition method is to do the same thing (mathematically) to both sides of the equation, with the aim of bringing like terms together and isolating the variable (or the unknown quantity). That is we group the ‘n’ terms one side and constants on the other side of the equation.

Complete step-by-step solution:
Given, \[7n - 5 = 5n + 7\].
We transpose ‘5n’ which is present in the right hand side of the equation to the left hand side of the equation by subtracting ‘5n’ on the left hand side of the equation.
\[7n - 5n - 5 = 7\]
\[2n - 5 = 7\]
We transpose negative 5 to the right hand side of the equation by adding 5 on the right hand side of the equation.
\[2n = 7 + 5\].
\[2n = 12\]
Divide the whole equation by 2,
\[n = \dfrac{{12}}{2}\]
\[ \Rightarrow n = 6\]
This is the required answer.

Note: We can check whether the obtained solution is correct or wrong. All we need to do is substituting the value of ‘n’ in the given problem.
\[7(6) - 5 = 5(6) + 7\]
\[42 - 5 = 30 + 7\]
\[ \Rightarrow 37 = 37\]
Hence the obtained answer is correct.
We know that the product of two negative numbers is a positive number. Product of a negative number and a positive number gives negative number (vice versa)
If we want to transpose a positive number to the other side of the equation we subtract the same number on that side (vice versa). Similarly if we have multiplication we use division to transpose. If we have division we use multiplication to transpose. Follow the same procedure for these kinds of problems.